Chemical-mineralogical features and physical properties of archaeological adobe: The evidence from Tell Zurghul/Nigin (Dhi Qar, Iraq) - Luca Volpi; Francesco Santoro De Vico; Anna Arizzi; Nicola Lanzaro; Davide Nadali (PLoS ONE, 2026)
This study examines the chemical, mineralogical, hydric, and mechanical properties of archaeological adobe bricks and earthen plasters from the site of Tell Zurghul/Nigin in southern Iraq, which are associated with recently excavated buildings dated to the 5 th and 3 rd millennium BCE. As integral components of earthen architecture, adobe structures are susceptible to rapid deterioration when subjected to environmental conditions and other degradation factors. Consequently, their preservation is a critical focus within cultural heritage initiatives involving earthen constructions. A comprehensive understanding of the materials used in buildings and their inherent properties is essential for identifying optimal conservation methods for archaeological earthen structures. The research is driven by two primary objectives. Firstly, it seeks to explore construction techniques within a diachronic framework, assessing their temporal evolution while considering the geological context and availability of local raw materials. Secondly, mineralogical and chemical analyses, alongside hydric and mechanical tests, aim to evaluate the characteristics of the adobe bricks, including their resistance and durability against weathering.